2015
DOI: 10.1088/1674-1056/24/10/103402
|View full text |Cite
|
Sign up to set email alerts
|

Site preferences and lattice vibrations of Nd 6 Fe 13 − x T

Abstract: The site preferences of the rare earth intermetallics Nd6Fe13−xTxSi (T = Co, Ni) are investigated by using interatomic pair potentials which are converted from a lattice-inversion method. Calculation shows that the order of the site preference of Co is 4d, 16k, 16l1, and 16l2 and that of Ni is 16l2, 16l1, 16k, and 4d in Nd6Fe13−xTxSi. Calculated lattice and positional parameters are found to agree with those reported in the literature. Furthermore, the phonon density of states for Nd6Fe13−xTxSi is also evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Some metal ions, such as Cd 2+ , Cu 2+ , Fe 3+ , and Hg 2+ ions, engendered a substantial loss of protease activity, but Mg 2+ , Ca 2+ , and K + ions augmented protease activity to some extent. Although metal ions may exert different effects on proteases from various resources, in general, Hg 2+ ions usually brought about loss in activity , and Mg 2+ , Ca 2+ , and K + ions were the most promising metal ions that could heighten protease activity . In the current study, some intriguing results were observed from treatments under Pb 2+ , Mn 2+ , and Al 3+ .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Some metal ions, such as Cd 2+ , Cu 2+ , Fe 3+ , and Hg 2+ ions, engendered a substantial loss of protease activity, but Mg 2+ , Ca 2+ , and K + ions augmented protease activity to some extent. Although metal ions may exert different effects on proteases from various resources, in general, Hg 2+ ions usually brought about loss in activity , and Mg 2+ , Ca 2+ , and K + ions were the most promising metal ions that could heighten protease activity . In the current study, some intriguing results were observed from treatments under Pb 2+ , Mn 2+ , and Al 3+ .…”
Section: Discussionmentioning
confidence: 56%
“…The protease from A. virgineoides displayed comparable K m value (3.74 mg/mL) as proteases isolated from Pleurotus citrinopileatus (3.44 mg/mL) and Helvella lacunose (3.81 mg/mL) , which means similar affinities toward casein were possessed by the above‐mentioned proteases. Nevertheless, A. virgineoides protease evinced a higher affinity than those proteases reported previously from Termitomyces albuminosus , Pholiota nameko , and Lepista nuda , with K m values being 8.26, 5.64, and 6.36 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The resulting expression data were analysed via GeneSpring GX (Agilent Technologies, Santa Clara, CA, USA) and filtered on expression and volcano plot (P < 0.05 and fold change>1.5). GO terms were determined by DAVID software (29)(30)(31).…”
Section: Microarray Analysismentioning
confidence: 99%
“…As indicated on Table S2, a selected number of the genes (7/15) were validated using relative quantity RT-PCR. DAVID software (29)(30)(31) was utilized to extract common molecular function gene ontology terms, and the list was divided into two groups containing the majority of the genes ( Figure S1a). The largest group contained 11 genes that were identified as being involved in protein-protein interactions (BAX, ADRA2C, UBAP2L, DAB2IP, EXTL3, ZBTB22, PDZD2, KLHL18 and ATF3), while the second group was a set of 6 genes that exhibit nucleotide-binding ability (IQCA1, KSR1, ULK4 and ZNF215).…”
Section: Putrescine Differentially Regulates Gene Expression In Keratmentioning
confidence: 99%